Thai Buddhist Families - Sutthirat, Netnapa (Journal of Dhamma for Life, 2021)
The study aims to discuss the main topic of Thai Buddhist Families. The family is also a source of nurturing political skills. Living legally has roles and responsibilities, respecting each other's rights, joint decision knowing, listening and communicating, reconciling with love, understanding, and reason, and knowing forgiveness. There is a separation of duties and responsibilities that divide work between families. That will see in the previous Thai society, even wives were inferior to husbands, but there were separate duties of husband and wife, such as the authority to make decisions outside the home to be a leader, while the burden of care. Houses and family members in the house are the wife's duty to take care of. For the elderly, it is responsible for training, teaching, and polishing child members have to learn how to live for inherits the family lineage.